Customer orientation as a psychological construct: evidence from Indian B-B salespeople. Issue 4 (11th September 2017) - Johlke, Mark C.; Iyer, Rajesh
Abstract : Purpose: The purpose of this paper is to extend Zablah et al. 's (2012) findings regarding the proper way to treat customer orientation (CO) to the study of CO among B-B salespeople in one of the most important emerging economies, India. Design/methodology/approach: The authors of this study hired a professional market research firm based in Chennai, a large metropolitan city in Southern India, to manage data collection. The authors used a competing models approach to test the relationship between constructs. Findings: CO among frontline employees operating in one of the largest emerging economies is best treated as a psychological construct that is both directly and indirectly related to performance via its ability to reduce stress and improve engagement. This finding strengthens the view of CO as a universal human work value and, more broadly, that such values operating across different cultural setting do exist. In addition, external customer mindset appears to offer a superior means to measure CO than does the widely used CO component of the SOCO scale. This conclusion is based not only upon the fact that it conceptually corresponds with the psychological nature of CO, but also that in this initial examination it exhibits a greater ability to explain employee job performance. Originality/value: Managers who are able to screen and hire employees with greater CO work values should experience improved performance outcomes and also less customer ambiguity and greater satisfaction among their frontline employees. Since CO proscribes the proper way to deal with customers, greater levels of CO beliefs would counteract customer ambiguity among frontline employees operating in any environment. Accordingly, when filling frontline positions, managers should actively seek out employees who earnestly embrace the role of taking care of customers. Managers are advised to not only emphasize on salespeople whose foremost role is to take care of their customers but also to find ways to familiarize them with their products and to provide them with information regarding customer characteristics such as their background, the relationship history (especially past service and product failures), and unique preferences.